Neutrophil apoptosis is delayed in an equine model of colitis: Implications for the development of systemic inflammatory response syndrome. (27th May 2016) - Anderson, S. L.; Singh, B.
Summary: Background: Horses that develop colitis invariably exhibit signs of a systemic inflammatory response syndrome (SIRS). A significant contributor to the development of SIRS in human subjects is delayed neutrophil apoptosis, but this has not been specifically studied in horses. Objectives: To determine the occurrence of ex vivo neutrophil apoptosis and its contribution to the development of SIRS in an equine colitis model. Study design: Experiment using a colitis model. Methods: Neutrophils were isolated before and after the induction of colitis using an oligofructose overdose model, placed into culture for 12 h or 24 h with or without lipopolysaccharide (LPS) at various concentrations, and assessed for the occurrence of apoptosis using Annexin V and propidium iodide staining with flow cytometric quantification. Levels of caspase‐3, ‐8 and ‐9 activity were measured after 12 h of incubation in neutrophil lysates. Results: Ex vivo neutrophil apoptosis was significantly delayed in neutrophils isolated after the induction of colitis (12‐h incubation: P = 0.004; 24‐h incubation: P = 0.003) with concomitant reductions in caspase‐3, ‐8 and ‐9 activity (caspase‐3: P = 0.004; caspase‐8: P = 0.02; caspase‐9: P = 0.02). Neutrophils isolated after the induction of colitis were refractory to LPS‐delayed apoptosis. Neutrophil apoptosis was delayed with increasing cell concentration in vitro . Main limitations: The main limitation of the study is the that the exact mechanism for delayed neutrophil apoptosis following the induction of colitis was not fully elucidated. Conclusions: The data show that neutrophil apoptosis is delayed in horses following the induction of colitis as a result of interference with the intrinsic and extrinsic apoptotic pathways, which may contribute to the development of equine SIRS. Concurrent development of neutrophilia may contribute to a prolonged neutrophil lifespan through a concentration‐dependent delay in apoptosis.